A study on perception and knowledge of farmers towards biofertilizer application in paddy farming in KADA, Kelantan. / Mohamad Asyraf Hazahan - Hazahan, Mohamad Asyraf (Faculty of Plantation and Agrotechnology, 2014)
Knowledge and perception of farmers is important factors that can influence them to replace the chemical fertilizer application with biofertilizer on plant. Biofertilizer is recommended for farmers to apply in paddy farming because it can improve the soil fertility, promote the paddy growth and conserve the environment. However in order to achieve that mission, it is important to know whether the knowledge and perception of farmers are really affecting them to apply the biofertilizer in their paddy field. The aims of this research project were to identify perception and knowledge level of farmers towards biofertilizer application in paddy farming and to identify the relationship between perception and knowledge towards biofertilizer application. This research was conducted at Kemubu Agricultural Development Authority (KADA), Kelantan under Development and Planning division. The respondents were asked about their perceptions and knowledge by using a Likert-type scale. The data collected was analysed by using Statistical Package for Social Sciences (SPSS Version 22). At the end of this study, result showed that the perception and knowledge level of farmers give significant effect to them to apply biofertilizer in their paddy field. But, the factor that more influences them is knowledge related to biofertilizer application. It is recommended to find out the perception and knowledge level of paddy farmers that operate the large scale of paddy plantation, purposely to obtain more perception or any brilliant idea that can improved and increase the yield production of paddy.